2006
DOI: 10.1093/annonc/mdl081
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus CI-994 offers no advantage over gemcitabine alone in the treatment of patients with advanced pancreatic cancer: results of a phase II randomized, double-blind, placebo-controlled, multicenter study

Abstract: Adding CI-994 to gemcitabine in advanced pancreatic carcinoma does not improve overall survival, response rate or time to progression; CG produced decreased QoL and increased hematological toxicity and appears inferior to single-agent gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 21 publications
0
51
0
1
Order By: Relevance
“…[17][18][19] Despite their relatively short history, HDAC inhibitors have realized both success and failure in clinical trials. For example, clinical trials in patients with pancreatic and lung cancer with the substituted benzamide derivative, CI-994 (acetyldinaline; Pfizer Global Research and Development, NY, USA) were abandoned due to inadequate efficacy, 20,21 even though the compound showed very promising effects in preclinical studies, particularly in combination with other conventional chemotherapeutics. 22 In contrast, SAHA (also known as vorinostat and marketed as Zolinza; Merck & Co. Inc., NJ, USA), depsipeptide (also previously known as FK288 or FK901228 and given the generic name Romidepsin; Gloucester Pharmaceuticals Inc., MA, USA) and numerous other compounds are progressing in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Despite their relatively short history, HDAC inhibitors have realized both success and failure in clinical trials. For example, clinical trials in patients with pancreatic and lung cancer with the substituted benzamide derivative, CI-994 (acetyldinaline; Pfizer Global Research and Development, NY, USA) were abandoned due to inadequate efficacy, 20,21 even though the compound showed very promising effects in preclinical studies, particularly in combination with other conventional chemotherapeutics. 22 In contrast, SAHA (also known as vorinostat and marketed as Zolinza; Merck & Co. Inc., NJ, USA), depsipeptide (also previously known as FK288 or FK901228 and given the generic name Romidepsin; Gloucester Pharmaceuticals Inc., MA, USA) and numerous other compounds are progressing in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…13) Interestingly, histone deacetylase (HDAC) inhibitors specifically induce the expression level of such anticancer genes as p21, TRAIL and FasL, DR5 and FAS in leukemia cells and not in normal cells. [14][15][16] The outstanding selective toxicity of such HDAC inhibitors as suberoylanilide hydroxamic acid (SAHA), 17) 4-(acetylamino)-N-(2-amiophenyl) benzamide (CI-994) 18,19) and cyclo[(2Z)-2-amino-2-butenoyl-L-valyl-(3S,4E)-3-hydroxy-7-mercapto-4-heptenoyl-D-valyl-D-cysteinyl], cyclic (3!5)-3-disulfide (FK-228) 20) might provide effective anticancer drugs in the near future. Most of such HDAC inhibitors, including trichostatin A (TSA), 21) show non-specific inhibitory activity against HDACs from both classes I and II.…”
mentioning
confidence: 99%
“…In vivo, however, this has not been shown. Phase II study of gemcitabine in combination with tacedinaline (a known HDAC-i) showed no improvement in patient response rate or survival compared to gemcitabine alone [26]. Thus search for effective HDAC-is continues.…”
Section: Discussionmentioning
confidence: 99%